The Healthcare Matrix: Improving Care by Linking Outcomes to Competencies - Doris Quinn (Association of American Medical Colleges, 2007)
Abstract The Healthcare Matrix provides learners with a structured framework to analyze complex episodes of patient care in terms of the Aims for Improvement standards outlined by the Institute of Medicine (OIM), and the Core Competencies identified by the Accreditation Council for Graduate Medical Education (ACGME). The 36-cell Matrix has one cell to represent each intersection of an IOM Aim for Improvement (identified in the IOM report, crossing the Quality Chasm) with an ACGME Core Competency. The individual cells of the Matrix allow the care analysis to be segmented into more manageable parts. By associating the IOM Aims with the ACGME Core Competencies, the Matrix encourages learners to reflect on the care they provide and determine the improvements needed, while helping them learn and apply the Aims and Competencies. If learners cannot identify issues in the bottom line of the Matrix (i.e., the Practice-Based Learning and Improvement field), then they have not sufficiently analyzed the care. Learners may then use this information to develop action plans that improve care from an individual and systems-perspective so that they experience first-hand the Practice-Based Learning Improvement Core competency. This tool provides a learning format that is part of the daily education and delivery of care by residents. It addresses the multidisciplinary culture that residents practice and may be used by many health professions students besides residents. By prompting users to consider system issues as well as medical knowledge, communication, and professionalism, the Matrix can change the evaluation of care from an atmosphere of "shame and blame" to an environment of collective analysis and improvement. Perhaps one of the greatest assets of the Matrix is its function as a mechanism to teach the competencies in a way that integrates education with outcomes of care (ACGME Outcomes Project Phase III requirements). Finally, it should be noted that this tool provides a solution that is standardized so that multiple programs and multiple institutions can have a common framework to teach the competencies and to learn from each other.